Secondary Merkel Cell Carcinoma Arising From a Graft Donor Site. Issue 2 (March 2017) - Aloraifi, Fatima; Mulgrew, Stephen; James, Nick K.
Merkel cell carcinoma (MCC) is a highly aggressive cutaneous neuroendocrine tumour that is increasing in incidence. We report a case of a 92-year-old white man on long-term immunosuppression for temporal arteritis who presented with a Merkel cell tumour on his left cheek. A wide local excision was performed and the defect was reconstructed with a full-thickness skin graft. Four years later, the patient re-presented with a Merkel cell tumour arising from the right supraclavicular donor site. To our knowledge, this is the first report of a recurrence of MCC into a donor site. This has important implications as a reminder of planning fresh surgical instruments and needle inoculation for reconstruction if there is any clinical suspicion of MCC to prevent iatrogenic spread.